2015
DOI: 10.1002/polb.23664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aromatic regularity on the structure and conductivity of polyimide‐poly(ethylene glycol) materials doped with ionic liquid

Abstract: An understanding of the structure and properties of polymer electrolyte systems can be crucial to a variety of different applications. The current work performs a study of the composition, structure and properties of poly(ethylene glycol) (PEG)-aromatic polyimide systems incorporating ionic liquids that are relevant to several applications especially fuel cell membranes. Composition was varied through using different aromatic dianhydrides, aromatic diamines and in some cases synthesis solvent. Properties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 69 publications
14
31
0
Order By: Relevance
“…As a result, the EAN‐doped PI‐PEG membranes can be considered as having two distinctly different phases; one is the rubbery PEG ( T g ≈ –70 °C) domain highly swollen with EAN [PEG+EAN] and the other is the glassy 6FDA‐PDODA PI ( T g ≈ 160 °C; see Figure S2 and the figure caption, Supporting Information) plasticized with EAN. Importantly, there was no evidence of crystalline PEG phase in the copolymer according to the DSC measurements (see Figure S2, Supporting Information for DSC data), as also noted in the previous work . The spatial confinement by covalent bonding to the PI chains seems to prevent the crystallization of PEG segments (see Figure d) …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As a result, the EAN‐doped PI‐PEG membranes can be considered as having two distinctly different phases; one is the rubbery PEG ( T g ≈ –70 °C) domain highly swollen with EAN [PEG+EAN] and the other is the glassy 6FDA‐PDODA PI ( T g ≈ 160 °C; see Figure S2 and the figure caption, Supporting Information) plasticized with EAN. Importantly, there was no evidence of crystalline PEG phase in the copolymer according to the DSC measurements (see Figure S2, Supporting Information for DSC data), as also noted in the previous work . The spatial confinement by covalent bonding to the PI chains seems to prevent the crystallization of PEG segments (see Figure d) …”
Section: Resultssupporting
confidence: 78%
“…Recent studies showed that segmented block copolymer (SBC) membranes comprised of aromatic polyimide (PI) and poly(ethylene glycol) (PEG) doped with an ionic liquid (IL) present an atractive potential to develop a new family of PEMs . In the PI‐PEG copolymer membranes, phase‐separated PEG domains swollen with IL act as the ion conducting phase and the PI phase serves as supporting matrix to provide for the required thermo‐mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to conduct explorations on 2 of 9 their structure-property relationships for practical applications. Although some studies showed that the chain hardness constituted the extremely crucial factor which affects their attributes in a direct way [19][20][21][22][23], the structure-property relationships links PIs are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because of the rigid structure of the aromatic polyimide, polymer has high softening temperature and processing temperature, which limits their processability. 6 10 As we all know, molecular structures have a strong effect on the properties of polymers. To overcome the weakness of the above-mentioned polymers, several efforts have been made worldwide to obtain a class of polyimides, which have good solubility and processability without impairing the performance and extending their technological applications in the industry.…”
Section: Introductionmentioning
confidence: 99%